MIDWIFERY STUDENT'S SATISFACTION ANALYSIS OF LABORATORY SERVICE WITH IMPORTANCE-PERFORMANCE ANALYSIS (IPA) METHOD AT STIK SITI KHADIJAH PALEMBANG - Meta Rosdiana; Rina Puspita (JURNAL KEBIDANAN, 2022)
The laboratory is a place to apply theory, apply theoretical knowledge, and so on, equipped with tools and facilities with adequate quantity and quality. Service quality/satisfaction is everything that focuses on the efforts made to meet the needs and desires of users accompanied by accuracy in delivering them to create balanced suitability with user expectations. This study aims to analyze the satisfaction of midwifery students with laboratory services using the Importance-Performance Analysis (IPA) method at STIK Siti Khadijah Palembang and as an evaluation material in maximizing the quality of the midwifery study program. Simple random sampling technique, covering 80 students of midwifery students at levels 1, 2, and 3 starting on August 9 to August 15, 2022. This study resulted in the quality of service received by students not as expected, still incomplete hand washing facilities that can be used, lack of available toilets, and places of worship in the laboratory besides the lack of internet facilities in this case internet access is not yet available or not all lecturers/students can access the internet in the midwifery laboratory, it is hoped that improvements can be made to the priority of attributes that are in quadrant 1.